An evaluation of differences in hip external rotation strength and range of motion between female dancers and non-dancers. Issue 6 (23rd November 2004) - Gupta, A; Fernihough, B; Bailey, G; Bombeck, P; Clarke, A; Hopper, D
Abstract : Objectives: To evaluate the differences in hip external rotation (ER) strength and inner, outer, and total hip ER range of motion (ROM) between dancers and non-dancers and between left and right sides in each group. Methods: Seventy one subjects (34 dancers and 37 non-dancers) volunteered for this study. The strength (truncated range average torque (TRAT), work, and angle specific torque (AST)) of the hip external rotator muscle group, through the full available active hip ER ROM, was evaluated using concentric isokinetic (30°/s) testing on a KinCom dynamometer. Adjustment for lean body mass (LBM) was made for comparison of strength between groups. A two way repeated analysis of covariance was used to compare strength between groups. A two way repeated analysis of variance was used to compare strength between sides and ROM between groups and sides. Bonferroni correction was made for multiple analyses, and significance was accepted at p⩽0.05. Results: AST at 0°, 20°, 30°, and 40° of hip ER was greater in the dancers than the non-dancers (p⩽0.022). TRAT, work, AST0°, AST20°, and AST30° of hip ER were all greater on the right side than the left (p = 0.007) in both groups. Dancers had greater inner ER ROM (p = 0.013) and less outer ER ROM than non-dancers (p⩽0.001). There was no difference in total ER ROM between groups (p = 0.133). The right side had greater inner ER (p⩽0.001) and total ER ROM (p⩽0.001) than the left in both groups. Conclusions: Ballet dancers have greater inner range, angle specific strength and inner range ER ROM, demonstrated by a shift in the dancers' strength curves. This shift in the strength curve towards the inner range of hip ER may be an adaptive training response.